Biological characterization of a fast growing non-sporing alkalophilic lignin degrading fungus MVI.2011 - Dev M S, Lipin; V, Thankamani (Research in Biotechnology, 2012)
MVI.2011 a rapidly multiplying alkalophilic non sporing fungus was isolated in 1990 and preliminarily identified as a Deuteromycete. The isolate was characterized in detail. The original isolate produced highly fluffy, cottony, fragile aerial mycelia on SDA and a similar growth in liquid SDB also. The organism grew out even on the surface of the conical flask containing the liquid medium inoculated indicating the high aerobic nature. With frequent sub culturing over 20 years the colony morphology on the same media appeared very confined with regular margin and dry surface. Yet there were no reproductive structures. LP staining showed dimorphism with apical fragmentation and no conidia, spores sexual or asexual etc. The pH range was very wide 5-11. The optimum cultural conditions for lignin degradation were pH 8.5, temperature 25-28oC, 12-18 hours and medium- 1% glucose, 0.5% peptone in basal mineral medium. The isolate could breakdown and decolourise commercial lignin (0.1-5%) and alkaline wood extract (1-50%) within 12-18 hours in static cultures evidenced by a clear reduction in absorption at 380 nm (lignin) and a marked shift to increased absorption at 360 nm and between 180 and 300 nm indicating appearance of lignin breakdown products. In optimisedÃ‚Â  media containing commercial lignin (0.1%) and alkaline wood extract (10%), MVI.2011 secreted Lignin peroxidase (9.39 units/ml), Manganese peroxidase (2.093 units/ml) and laccase (3.5 units/ml) enzymes. TheÃ‚Â  above data led us to conclude that the isolate was novel being highly alkalophilic, capable of rapid growth, decolourisation of lignins andÃ‚Â  secretion of lignin degrading enzymes. Based on microscopic morphology and colony features, the isolate coded MVI.2011 has been identified as Ã¢â‚¬Å“Uncultured FungusÃ¢â‚¬Â with NCBI Accession No JN606084. It has beenÃ‚Â  deduced to be a member of Mycelia sterilia group.